The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1177/000494410304700203
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the United States Educational Administrator Shortage

Abstract: here are multiple independent and interactive factors that may contribute to perceptions o r misperceptions concerning an administrator shortage in the T United States (US). These factors include the complexities of supply and demand data, inferential errors and over-generalisations, candidate quantity issues confounded by anecdotal accounts of candidate quality, administrator accounts of limited job desirability, and the 'invisibility' of women administrators as a viable candidate pool. Some researchers have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 13 publications
(11 reference statements)
0
16
0
Order By: Relevance
“…On the other hand, Pounder, Galbin, and Shepherd (2003) have questioned the evidence provided that points to a perceived shortage of candidates for open principal positions. These authors believe that the evidence claiming such a shortage is anecdotal, inconsistent, and inconclusive.…”
Section: Calls For Reformmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, Pounder, Galbin, and Shepherd (2003) have questioned the evidence provided that points to a perceived shortage of candidates for open principal positions. These authors believe that the evidence claiming such a shortage is anecdotal, inconsistent, and inconclusive.…”
Section: Calls For Reformmentioning
confidence: 99%
“…These authors believe that the evidence claiming such a shortage is anecdotal, inconsistent, and inconclusive. Pounder et al (2003) suggested that, while there may indeed be certain shortages for specific openings (e.g., high school principalships and superintendencies), and in certain locations (e.g., rural communities and large urban areas), such shortages in these types of positions and locations are specific to these areas and should not be generalized across the entire field.…”
Section: Calls For Reformmentioning
confidence: 99%
See 1 more Smart Citation
“…They argue that new forms of governance, role expansion and work intensification have had the effect of reconstructing leadership as a form of 'greedy work' which individuals are increasingly less willing to undertake. Others have suggested that the 'leadership crisis' may be politically and ideologically constructed (Pounder et al 2003).…”
Section: Factors Influencing Applications For Headshipmentioning
confidence: 99%
“…Over the past decade, there has been much debate about the existence of a shortage of qualified school principals as a result of the large number of principals retiring, changing positions, or leaving the profession (Gates, Ringel, Santibanez, Ross & Chung, 2003;Pounder, Galvin & Sheppard, 2003). Shelton (2012) cited information from The National Commission on Teaching and America's Future that stated more than half of the country's principals were baby boomers born between 1946 and 1964 and projected that schools could lose one-third of their most accomplished and experienced leaders to retirement by 2019.…”
Section: Introductionmentioning
confidence: 99%